Peningkatan Kapasitas Guru Dalam Pemberian Motivasi Belajar Siswa Pada Pembelajaran Daring di SDN PLUIT 01 dan 05 - Clara Ika Sari Budhayanti; Maria Magdalena Triwarmiyati DW; Lorensius Noel Praba; Vinny Magdalena (MADANI: Jurnal Pengabdian Kepada Masyarakat, 2021)
One of the weaknesses of online learning is the lack of learning interactions, both interactions between teachers and students, students and students, and media and learning resources. Teachers tend to give assignments that must be completed independently by students. Learning interactions only occur at the time of giving and collecting duties. This lack of learning interaction resulted in the learning process running monotonous and less varied.  This condition causes students to be lazy to study and bored. So, they are not motivated to learn. If this is allowed to continue, it will affect student achievement. Therefore, teachers need to change online learning patterns by changing learning methods, using various learning media, and intensifying learning activities to increase students' motivation. Implementing this activity uses the lecture, discussion, and assignment methods that aim to provide an overview and help teachers at SDN 01 and 05 Pluit design online learning that fosters and increases student motivation. The results of this activity are pretty good, as expected. The training participants can fully understand how students' learning motivation is to design lessons that motivate students. Some teachers have been able to choose various learning media that can attract students' attention so that students do not get bored in participating in learning. The follow-up to this activity is more intensive assistance to teachers in planning implementation and conducting learning assessments.